Diameter-driven crossover in resistive behaviour of heavily doped self-seeded germanium nanowires - Connaughton, Stephen; Koleśnik-Gray, Maria; Hobbs, Richard; Lotty, Olan; Holmes, Justin D.; Krstić, Vojislav (Beilstein Journal of Nanotechnology, 2016)
The dependence of the resistivity with changing diameter of heavily-doped self-seeded germanium nanowires was studied for the diameter range 40 to 11 nm. The experimental data reveal an initial strong reduction of the resistivity with diameter decrease. At about 20 nm a region of slowly varying resistivity emerges with a peak feature around 14 nm. For diameters above 20 nm, nanowires were found to be describable by classical means. For smaller diameters a quantum-based approach was required where we employed the 1D Kubo–Greenwood framework and also revealed the dominant charge carriers to be heavy holes. For both regimes the theoretical results and experimental data agree qualitatively well assuming a spatial spreading of the free holes towards the nanowire centre upon diameter reduction.
Keywords: diameter-dependence; germanium; nanowire; resistivity; self-seeded